Experimental and numerical studies on a test method for damage diagnosis of stay cables. Issue 2 (February 2017) - An, Yonghui; Zhong, Yue; Tan, Yanbin; Ou, Jinping
To diagnose the state of stay cables, a vibration-based model-free damage diagnosis method of stay cables using the changes in natural frequencies is further proposed and validated. The structural frequency is rapidly and easily acquired; moreover, it is simple and reliable for damage diagnosis. The frequency would change after the stay cable is damaged, so the frequency change could be used as the damage index. However, the stay cables are very long in long-span cable-stayed bridges, and their frequencies are very small; the frequency change due to small damage of the stay cable would be submerged by the surrounding noise and error of parameter identification process. A temporary diagonal steel bar–based method is used to solve this issue. The steel bar is installed with one end on the stay cable close to the bottom anchor head and the other end on the bridge deck; thus, the stay cable is divided into a short part and a long part by the steel bar. The frequency of a stay cable with a given tension force increases with the decrease in its length; according to the qualitative analysis, the frequency of the short part increases dramatically, and the local frequency change of the short part due to the same damage in the whole stay cable is amplified dramatically; thus, the small damage of a stay cable can be diagnosed easily. Numerical simulations of a stay cable selected from a cable-stayed bridge and a laboratorial stay cable are used to validate the method and also give a recommended rule for design of the temporary diagonal steel bar; experimental validation has also been conducted. All the results indicate that the proposed method works very well in damage diagnosis of stay cables. The proposed method is an output-only, model-free, fast and economical damage diagnosis method for stay cables.